1997
DOI: 10.1074/jbc.272.47.29801
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Transcriptional Regulatory Element Common to the p53 and Interferon Regulatory Factor 1 Genes

Abstract: The promoter regions of both the interferon regulatory factor (IRF1) and p53 antioncogenes contain a previously unidentified sequence denoted IRF1 p53 common sequence (IPCS), which markedly increases the transcriptional activity of a reporter gene placed under the control of an heterologous promoter in transfected U937 cells. In contrast, transfection of U937 cells with reporter vectors containing p53 and IRF1 promoters with mutated IPCS sites resulted in a 4-fold reduction in the constitutive expression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…IFN dosage was performed as previously described (22). Each sample was tested in duplicate and the dosage was repeated twice.…”
Section: Methodsmentioning
confidence: 99%
“…IFN dosage was performed as previously described (22). Each sample was tested in duplicate and the dosage was repeated twice.…”
Section: Methodsmentioning
confidence: 99%
“…The transcriptional activity of IPCS was shown to be strictly correlated with the binding of an IPCSbinding factor (IPCS-BF), thereby revealing that the expression of these two growth suppressive genes is under common regulation (Lallemand et al, 1997).…”
Section: Terminal DI Erentiation Negative Growth Control and Myd Genesmentioning
confidence: 99%
“…Transcriptional activation of IPCS is strictly dependent on the binding of an IPCS-binding factor (IPCS-BF), indicating that expression of these two growth suppressive genes is also under common regulation. 29 Taken together, what has been discussed above suggests that IRF-1 functions as a tumor suppressor gene whose loss of function contributes to oncogenesis. Consistent with this notion, Harada et al 30 have shown that balanced expression of IRF-1 and IRF-2 is critical for normal cell growth.…”
Section: Spotlightmentioning
confidence: 99%